Biological Landscape of Triple Negative Breast Cancers Expressing CTLA-4 - Navarrete-Bernal, María G. C.; Cervantes-Badillo, Mayte G.; Martínez-Herrera, Jose Fabián; Lara-Torres, César O.; Gerson-Cwilich, Raquel; Zentella-Dehesa, Alejandro; Ibarra-Sánchez, María de Jesús; Esparza-López, José; Montesinos, Juan J.; Cortés-Morales, Víctor Adrián; Osorio-Pérez, Diego; Villegas-Osorno, Diana A.; et al. (Frontiers in Oncology, 2020)
Patients with triple-negative breast cancer (TNBC) have a poor prognosis, partly because of the absence of targeted therapies. Recognition of the key role of immune responses against cancer has allowed the advent of immunotherapy, focused on the inhibition of negative immune checkpoints, such as CTLA-4. CTLA-4 is also expressed in some cancer cells, but its activity in tumor cells not completely understood. Thus, the aim of the present work was to determine the biological landscape and functions of CTLA-4 expressed in TNBC cells through preclinical and in-silico analysis. Exploration of CTLA-4 by immunohistochemistry in 50 TNBC tumors revealed membrane and cytoplasmic expression at different intensities. Preclinical experiments, using TNBC cell lines showed that stimulation of CTLA-4 with CD80 enhances activation of the ERK1/2 signaling pathway, while CTLA-4 blockade by Ipilimumab induces the activation of AKT and reduces cell proliferation in vitro. We then developed an analytic pipeline to define the effects of CTLA-4 in available public data that allowed us to identify 4 distinct tumor clusters associated to CTLA-4 activation, which are characterized by enrichment of distinctive pathways associated with cell adhesion, MAPK signaling, TGF-ß, VEGF, TNF-α, drug metabolism, ion and amino acid transport, KRAS signaling, among others. In addition, blockade of CTLA-4 induced increased secretion of IL-2 by tumor cells, suggesting that the receptor regulates cellular functions that may impact the immune microenvironment. This is relevant because a deep characterization of immune infiltrate, conducted using public data to estimate the abundancies of immune-cell types showed that CTLA-4 activated-like tumors present a conditional immune state similar to an escape phenotype exploited by cancer cells. Finally, by interrogating transcriptional predictors of immunotherapy response, we defined that CTLA-4 activation correlates with high immune scores related to good clinical predicted responses to anti-CTLA-4 therapy. This work sheds new light on the roles of activated CLTA-4 in the tumor compartment and suggests an important interplay between tumor CLTA-4 activated portraits and immune infiltrating cell-populations.